Enabling minimal invasive parathyroidectomy for patients with primary hyperparathyroidism using Tc-99m-sestamibi SPECT–CT, ultrasound and first results of 18F-fluorocholine PET–CT. Issue 9 (September 2015) - Kluijfhout, Wouter P.; Vorselaars, Wessel M.C.M.; Vriens, Menno R.; Borel Rinkes, Inne H.M.; Valk, Gerlof D.; de Keizer, Bart
Highlights: We examined an optimal pre-operative imaging strategy. Goal was to perform minimal invasive parathyroidectomy. Ultrasound significantly decreased the PPV when added to SPECT–CT. 18 F-fluorocholine was positive in 4/5 cases with negative conventional imaging. Abstract: Objective: Assessment of the diagnostic value of ultrasound (US), single photon-emission computed tomography–computed tomography (SPECT–CT) and 18 F-fluorocholine (FCH) PET–CT for preoperative localization of hyper-functioning parathyroid(s) in order to create a more efficient diagnostic pathway and enable minimal invasive parathyroidectomy (MIP) in patients with biochemical proven non-familial primary hyperparathyroidism (pHPT). Methods: A single-institution retrospective study of 63 consecutive patients with a biochemical diagnosis of non-familial pHPT who received a Tc-99m-sestamibi SPECT–CT and neck ultrasound. Surgical findings were used in calculating the sensitivity and the positive predictive value (PPV) of both imaging modalities. Furthermore we present 5 cases who received additional FCH PET–CT. Results: A total of 42 (66.7%) patients underwent MIP. The PPV and sensitivity of SPECT–CT, 93.0% and 80.3%, were significantly higher than those of US with 78.3% and 63.2%, respectively. Adding US to SPECT–CT for initial pre-operative localization did not significantly increase sensitivity but did significantly decrease PPV. Performance of US was significantly better when performed after SPECT–CT. 18 F-fluorocholine PET–CT localized the hyper-functioning parathyroid gland in 4/5 cases with discordant conventional imaging, enabling MIP. Conclusion: SPECT–CT is the imaging modality of choice for initial pre-operative localization of hyper-functioning parathyroid gland(s) in patients with biochemical pHPT. Ultrasound should be performed after SPECT–CT for confirmation of positive SPECT–CT findings and for pre-operative marking allowing MIP. In cases with negative or discordant imaging additional FCH PET–CT should be considered since this might enable the surgeon to perform MIP.